HERMENEUTIKA : Persoalan Filosofis – Biblis Penggalian Makna Tekstual - Simamora, Serpulus (UNIKA Santo Thomas, 2005)
To define what human being is one could present various definitions. Aristotle, for instance, defines the human being as animal rationale. One can, however, say that the human being is a hermeneutical being. Since its coming into existence the human being is dealing and will deal with hermeneutical act of interpretation. This act of interpretation is usually called hermeneutics. Generally speaking the hermeneutics is the act of human being in interpreting realities in life. Strictly speaking, however, it deals with interpretation of textual reality. In philosophical domain, the hermeneutics seeks to account for the philosophical ground of the act of interpretation. What is the ground of our intrepretation so that the interpretation may be accepted valid and true?